Personal identity in the dictator game - Fernando Aguiar; Pablo Bra\~nas-Garza; María Paz Espinosa; Luis M. Miller (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper aims to analize the role of personal identity in decision making. To this end, it starts by reviewing critically the growing literature on economics and identity. Considering the ambiguities that the concept of social identity poses, our proposal focuses on the concept of personal identity. A formal model to study how personal identity enters in individuals utility function when facing a Dictator Game decision is then presented. Finally, thisidentity-based utility function is studied experimentally. The experiment allow us to study the main parameters of the model, suggesting that we should move with caution when attributing identities to individuals.
Keywords: A13; C72; C91; 330; personal identity; dictator game; game theory; experiments; Nichtkooperatives Spiel; Verhandlungstheorie; Persönlichkeitspsychologie; Test